Unleashing ChatGPT: Redefining technology acceptance and digital transformation in higher education - Loubna Mourtajji; Nathalie Arts-Chiss (Administrative Sciences, 2024)
This article examines the effects of integrating ChatGPT, a generative language model developed by OpenAI, into educational and training contexts in higher education. The research takes as its conceptual framework models of technology acceptance and questions the relevance of these models to the acceptance and adoption of ChatGPT. A qualitative study carried out with teachers from various higher education establishments in France enables us to propose a model adapted to the specific features of generative AI. The ethical dimension and the controllability of the tools by users, made possible by a progressive training program, are two constructions that are essential to a proper understanding of whether or not these new tools are adopted. Additionally, this research contributes to the growing discourse on how generative AI innovations can be leveraged to enhance digital transformation in the academic sector, with a particular focus on business schools' stakeholders and strategies. Finally, the contributions and prospects for future research are discussed.
Keywords: 350; ChatGPT; education; TAM; qualitative survey